Biohythane production from food waste in a two-stage process: assessing the energy recovery potential. Issue 14 (20th June 2022) - Ghimire, Anish; Luongo, Vincenzo; Frunzo, Luigi; Lens, Piet N. L.; Pirozzi, Francesco; Esposito, Giovanni
ABSTRACT : Biohythane (hydrogen + methane) production in a two stage dark fermentation (DF) and anaerobic digestion (AD) process from food waste (FW) has been studied. This paper investigated the effect of operation temperature, i.e. mesophilic (34 °C) and thermophilic (55 °C) , on biohythane yield and total energy recovery carried out at the initial culture pH 5.5 and pH 7, respectively for DF and AD batch tests. The mesophilic DF tests gave a higher hydrogen yield of 53.5 ( ± 4) mL H2 /g VS added compared to thermophilic DF tests, i.e. 37.6 ( ± 1) mL H2 /g VS added. However, higher methane yields, i.e. 307.5 ( ± 10) mL CH4 /g VS, were obtained at thermophilic AD tests compared to mesophilic AD, i.e. 276.5 ( ± 4.3) mL CH4 /g VS. The total energy recovery from thermophilic DF + AD was higher (11.4 MJ/kg VS) than the mesophilic (10.4 MJ/kg VS) combined process. Interestingly, the analysis of kinetic parameters of mesophilic tests, determined from the Modified Gompertz equation, showed that mesophilic DF had faster H2 production kinetics, which can be attributed to a faster adaptation of the heat-shocked inoculum used in the tests to the incubation temperature. However, thermophilic AD tests exhibited faster kinetics for methane production. GRAPHICAL ABSTRACT: UF0001